A new procedure to measure children's reading speed and accuracy in Italian. (30th September 2013) - Morlini, Isabella; Stella, Giacomo; Scorza, Maristella
<x xml:space="preserve">Abstract</x> Impaired readers in primary school should be early recognized, in order to asses a targeted intervention within the school and to start a teaching that respects the difficulties in learning to read, to write and to perform calculations. Screening procedures, inside the primary schools aimed at detecting children with difficulties in reading, are of fundamental importance for guaranteeing an early identification of dyslexic children and reducing both the primary negative effects—on learning—and the secondary negative effects—on the development of the personality—of this disturbance. In this study, we propose a new screening procedure measuring reading speed and accuracy. This procedure is very fast (it is exactly 1 min long), simple, cheap and can be provided by teachers without technical knowledge. On the contrary, most of the currently used diagnostic tests are about 10 min long and must be provided by experts. These two major flaws prevent the widespread use of these tests. On the basis of the results obtained in a survey on about 1500 students attending primary school in Italy, we investigate the relationships between variables used in the screening procedure and variables measuring speed and accuracy in the currently used diagnostic tests in Italy. Then, we analyse the validity of the screening procedure from a statistical point of view, and with an explorative factor analysis, we show that reading speed and accuracy seem to be two separate symptoms of the dyslexia phenomenon. Copyright © 2013 John Wiley & Sons, Ltd.